2021
DOI: 10.3390/socsci10080279
|View full text |Cite
|
Sign up to set email alerts
|

Digital Overload among College Students: Implications for Mental Health App Use

Abstract: Mental health phone applications (apps) provide cost-effective, easily accessible support for college students, yet long-term engagement is often low. Digital overload, defined as information burden from technological devices, may contribute to disengagement from mental health apps. This study aimed to explore the influence of digital overload and phone use preferences on mental health app use among college students, with the goal of informing how notifications could be designed to improve engagement in mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 38 publications
(53 reference statements)
0
17
0
1
Order By: Relevance
“…Similarly, experience with a self-help program with brief coach support, a type of DMHI with considerable evidence-base, was modest. Recently, U.S. college students have described using games, entertainment apps, and social media apps to manage their mental health, as opposed to, for example, evidence-based apps targeting specific problems ( Smith et al, 2021 ). Students' views and uptake of DMHIs may be different and extend beyond evidenced-based DMHIs prioritized by policy makers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, experience with a self-help program with brief coach support, a type of DMHI with considerable evidence-base, was modest. Recently, U.S. college students have described using games, entertainment apps, and social media apps to manage their mental health, as opposed to, for example, evidence-based apps targeting specific problems ( Smith et al, 2021 ). Students' views and uptake of DMHIs may be different and extend beyond evidenced-based DMHIs prioritized by policy makers.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with clients' and clinicians' understanding of DMHIs, we included text and other synchronous messaging as a DMHI ( Lattie et al, 2020 ). We also examined potential technology-related determinants of using DMHIs (e.g., data plans; digital overload ( Misra and Stokols, 2011 ; Smith et al, 2021 )). Qualitative data included open-ended comments about standard mental health services and a self-help program with brief coach guidance.…”
Section: Methodsmentioning
confidence: 99%
“…Although only a minority of focus group participants commented on the "time gating" involved in RuminAid (ie, restricting users from moving from one quest to the next for a period of 1 week), this feedback highlighted potential frustration and loss of interest that might result from this restriction. This is reflected in the literature, which indicates that people use phone apps sporadically [23,[88][89][90], and in lay commentary, which suggested that people dislike apps and games with time-gated content [91]. In addition, attrition tends to be high in mHealth interventions [92][93][94].…”
Section: Principal Findingsmentioning
confidence: 99%
“…With multiple learning systems and faculty management systems guiding the entire process, the college students’ entire academic careers are being digitized. This “digital overload” potentially negatively impacts the mental health of college students [ 9 ].…”
Section: Introductionmentioning
confidence: 99%